Acute presentation of a benign cystadenofibroma of the fallopian tube: a case report - de Silva, Tania S (BioMed Central, 2010)
INTRODUCTION: Cystadenofibromas are rare benign tumors of the fallopian tube with only 15 reported cases worldwide. They are usually asymptomatic and are found incidentally. This case is presented on account of its rarity and to the best of our knowledge, is the first reported case of cystadenofibroma of the fallopian tube discovered during an appendicectomy. CASE PRESENTATION: We report a rare case of cystadenofibroma of the fallopian tube in a 19-year-old Caucasian woman who presented with sudden onset of right iliac fossa pain. A clinical diagnosis of appendicitis was made and she was taken to the operating theater for an appendicectomy. Intraoperatively, the appendix appeared normal. However, the 8 cm cyst contained within the right ovary and the blood in the pelvis warranted a salpingo-oopherectomy. Our patient made an uneventful recovery and was discharged after four days. Histology revealed a benign cystadenofibroma of the fallopian tube. There was no evidence of recurrence in the follow-up period of 12 months. CONCLUSION: Cystadenofibromas are benign tumors that may macroscopically and ultrasonographically appear malignant. We recommend that the diagnosis of cystadenofibroma is considered prior to performing radical surgery that may affect the fecundity of these patients. Cystadenofibromas confined to the fallopian tube can be treated curatively with unilateral salpingo-oophorectomy, without the need for any further treatment. However, long-term follow-up of more cases is required to draw more definitive conclusions.